Traumatic bilateral patellar ligament rupture without predisposing systemic disease or steroid use. Case Report - Campos Fernandes, Rafael de Souza (2008)
The authors report the rare occurrence of a traumatic bilateral patellar ligament rupture without predisposing systemic disease or steroid use in a 27 year-old patient, describing the chosen therapeutic approach and the follow-up.